2018
DOI: 10.2528/pierm18070508
|View full text |Cite
|
Sign up to set email alerts
|

Salient Pole Synchronous Generator Optimization by Combined Application of Slot Skew and Damper Winding Pitch Methods

Abstract: Slot skew is applied as a method to increase the armature winding voltage waveform quality of synchronous hydro generators. Skew that matches the region of one slot pitch can effectively damp stator slot harmonics. However, achieving this condition can be difficult in some manufacturing cases, especially for the machines with greater axial length. That is why other methods are commonly used to increase the voltage waveform quality of large hydro generators. One such method is based on the damper winding slot p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…There are also remarkable studies those are discussed the effect of damper winding on the SG in their studies [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…There are also remarkable studies those are discussed the effect of damper winding on the SG in their studies [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They used FEM for the simulations. Elez et al [19] presented a study on optimization of salient-pole SG. To that end they combined slot skew and damper winding pitch methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that with this optimization method, the damper bar losses can be reduced by 7 times and the total harmonic distortion can be reduced below 1%. [5]. In [1], the shape of the rotor is optimized to facilitate the assembly of excitation windings.…”
Section: Introductionmentioning
confidence: 99%